Conditional switching of KIF2A mutation provides new insights into cortical malformation pathogeny. (10th January 2020) - Gilet, Johan G; Ivanova, Ekaterina L; Trofimova, Daria; Rudolf, Gabrielle; Meziane, Hamid; Broix, Loic; Drouot, Nathalie; Courraud, Jeremie; Skory, Valerie; Voulleminot, Paul; Osipenko, Maria; Bahi-Buisson, Nadia; et al.
Abstract: By using the Cre-mediated genetic switch technology, we were able to successfully generate a conditional knock-in mouse, bearing the KIF2A p.His321Asp missense point variant, identified in a subject with malformations of cortical development. These mice present with neuroanatomical anomalies and microcephaly associated with behavioral deficiencies and susceptibility to epilepsy, correlating with the described human phenotype. Using the flexibility of this model, we investigated Rosa Cre -, Nestin Cre - and Nex Cre - driven expression of the mutation to dissect the pathophysiological mechanisms underlying neurodevelopmental cortical abnormalities. We show that the expression of the p.His321Asp pathogenic variant increases apoptosis and causes abnormal multipolar to bipolar transition in newborn neurons, providing therefore insights to better understand cortical organization and brain growth defects that characterize KIF2A-related human disorders. We further demonstrate that the observed cellular phenotypes are likely to be linked to deficiency in the microtubule depolymerizing function of KIF2A.